2020
DOI: 10.3390/md18080397
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Sulfated Galactans from Eucheuma serra and Gracilari verrucosa against Diarrheagenic Escherichia coli via the Disruption of the Cell Membrane Structure

Abstract: Seaweed sulfated polysaccharides have attracted significant attention due to their antibacterial activity. This work investigated the antibacterial activity and mechanism of depolymerized sulfated galactans from Eucheuma serra (E. serra) and Gracilaria verrucosa (G. verrucosa) against enterotoxigenic Escherichia coli (ETEC) K88. The results show that removing the metal ions improves the anti-ETEC K88 activity of the galactans. The fluorescence labeling study confirmed that the sulfated galactans penetrated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…For example, Margaritifera Concha has now been demonstrated to be effective against influenza and herpes viruses [ 108 ]. Pharmacological effects, such as inflammation [ 109 ], an anticoagulant effect [ 110 ], an antiallergic [ 111 ], an antibacterial [ 112 ], and even the treatment of obsessive-compulsive disorder [ 113 ], etc., have all been verified.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Margaritifera Concha has now been demonstrated to be effective against influenza and herpes viruses [ 108 ]. Pharmacological effects, such as inflammation [ 109 ], an anticoagulant effect [ 110 ], an antiallergic [ 111 ], an antibacterial [ 112 ], and even the treatment of obsessive-compulsive disorder [ 113 ], etc., have all been verified.…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal flora and its short-chain fatty acid (SCFAs) metabolites play an essential role in many inflammatory and immune diseases, such as arthritis, asthma, inflammatory bowel disease, allergic diseases, and colon cancer [ 39 ]. According to recent studies, DESP can specifically inhibit the growth of ETEC-K88 but have no such effect on probiotic bacteria [ 40 ], exhibiting the potential for treating bacterial diarrhea induced by ETEC-K88. Therefore, it is worth exploring the mechanism of DESP involved in bacterial diarrhea from the perspective of intestinal flora.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the growth of these two Gram-negative bacteria was inhibited by the anionic polysaccharide DESP. Furthermore, previous research confirmed that DESP can specifically inhibit the growth of Gram-negative bacteria, ETEC, but has no noticeable effect on the growth of Gram-positive bacteria and yeast [ 40 ]. This study showed that, compared with the model group, DESP effectively enriched the abundance of Lactobacillaceae , Bifidobacteriaceae , and Lachnospiraceae and inhibited the growth of Enterobacteriaceae and Bacteroidaceae in intestinal, which is similar to the regulation of fucoidan on the intestinal flora [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, Figure 8 shows the workflow of this study. In this study, a virtual screening of the marine small molecule library was initiated to identify a new S. aureus inhibitor from the marine small molecule library [30,31]. Through virtual screening, similarity screening and ADME drug analysis, we finally selected 46604 and 46608 as possible drug molecules targeting MurD enzyme of S. aureus.…”
Section: Discussionmentioning
confidence: 99%